A novel and effective ECG method to differentiate right from left ventricular outflow tract arrhythmias: Angle-corrected V2S - Qiu, Shifeng; Sun, Zhuhua; Li, Xinzhong; Li, Jianyong; Huang, Xiaobo; Liu, Menghui; Bin, Jianping; Liao, Yulin; Xiu, Jiancheng; Zha, Daogang; Xue, Yumei; Wang, Lichun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims: Standard 12-lead electrocardiogram (ECG) patterns combined with the anatomical cardiac long-axis angle revealed by chest X-ray can prevent the influence of cardiac rotation, physical shape and lead position, so it may be an ideal means to predict the origin of outflow tract (OT) ventricular arrhythmias (OTVAs) for ablation procedures. The study explores the value of this strategy in identifying the origin of OTVA. Methods: This study was conducted using a retrospective cohort and a prospective cohort of consecutive patients at two centres. The anatomical cardiac long-axis angle was calculated by measuring the angle between the cardiac long-axis (a line joining the apex to the midpoint of the mitral annulus) and the horizontal plane on chest X-ray. The V2S angle was calculated as the V2S amplitude times the angle. We ultimately enrolled 147 patients with symptomatic OTVAs who underwent successful radiofrequency catheter ablation (RFCA) (98 female (66.7%); mean age 46.9 ± 14.7 years; 126 right ventricular OT (RVOT) origins, 21 left ventricular OT (LVOT) origins) as a development cohort. The new algorithm was validated in 48 prospective patients (12 males (25.0%); mean age 48.0 ± 15.8 years; 36 RVOT, 12 LVOT origins). Results: Patients with RVOT VAs had greater V2S, long-axis angle, and V2S angle than LVOT VA patients (all P < 0.001). The cut-off V2S angle obtained by ROC curve analysis was 58.28 mV° for the prediction of RVOT origin (sensitivity: 85.7%; specificity: 95.2%; positive predictive value: 99.1%; negative predictive value: 52.6%). The AUC achieved using the V2S angle was 0.888 (P < 0.001), which was the highest among all indexes (V2S/V3R: 0.887 (P < 0.016); TZ index: 0.858 (P < 0.001); V1-2 SRd: 0.876 (P < 0.001); V3 transition: 0.651 (P < 0.001)). In the prospective cohort, V2S angle had a high overall accuracy of 93.8% and decreased the procedure time (P = 0.002). Conclusion: V2S angle can be a novel measure that can be used to accurately differentiate RVOT from LVOT origins. It could help decrease ablation duration and radiation exposure.